2002
DOI: 10.1002/joc.818
|View full text |Cite
|
Sign up to set email alerts
|

Changes in European spring phenology

Abstract: The European phyto-phenological database of the EU 5th Framework project 'POSITIVE' facilitated an examination of the rate and spatial pattern of changes in spring phenology across Europe. This database was collected, evaluated and composed from different national databases of Eastern and Western Europe covering the time period . Results show that spring phases have advanced four weeks in Western and Central Europe, and have been delayed up to two weeks in Eastern Europe. Western European spring starts earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
140
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(164 citation statements)
references
References 17 publications
19
140
1
4
Order By: Relevance
“…Namely, higher (lower) temperature from late winter to early spring tends to lead to earlier (later) flowering (Ahas et al, 2002;Zhang et al, 2004;Ho et al, 2006). The period when temperature has most influence on FFD depends on regional climatological conditions and varies among plant species.…”
Section: Early Spring Temperature Changementioning
confidence: 99%
“…Namely, higher (lower) temperature from late winter to early spring tends to lead to earlier (later) flowering (Ahas et al, 2002;Zhang et al, 2004;Ho et al, 2006). The period when temperature has most influence on FFD depends on regional climatological conditions and varies among plant species.…”
Section: Early Spring Temperature Changementioning
confidence: 99%
“…However, we can offer one suggestion of a likely situation in which such a development may have already started. It has recently been shown that elevated CO 2 levels and global warming can alter flowering phenology and flower nectar volumes in certain plant species (Erhardt and Rusterholz 1997;Ahas et al 2002;Fitter and Fitter 2002;Inouye et al 2002;Dunne et al 2003). Phenologies of different species appear to be shifting to different degrees, and in different directions: for example, Fitter and Fitter (2002) report that while 16% of British flowering plants are flowering significantly earlier than in previous decades (with an average advancement of 15 days in a decade), another 3% of species are flowering significantly later than they once did.…”
Section: Hawaiian Honeycreeper (Iiwi)mentioning
confidence: 99%
“…Since the second half of the 20 th century in many places of Europe, changes of average phenological dates have been observed in both the world of wild-growing and crop plants (Ahas et al, 2002;Bonofiglio et al, 2009;Chmielewski et al, 2004;Menzel, 2000;Menzel & Estrella, 2001). The most frequently shown direction of change has been in the acceleration of phenological dates, especially in relation to spring and summer dates.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-20 th century changes in air temperature values have had influence on the course of the growth and development of plants. All over the world research studies focused on the reactions of fruit trees (Chmielewski et al, 2004;Fujisawa & Kobayashi, 2010), wild-growing plants (Gordo & Sanz, 2009;Kalvāne et al, 2009;Moiseev et al, 2010;Yoshie, 2010), and crop plants ( Ahas et al, 2002;Dalezios et al, 2002;Kalbarczyk, 2009a;Mazurczyk et al, 2003;Menzel, 2000) have been conducted. Changes in temperature values lead to changes in duration of particular stages and the whole growing season of plants (Peiris et al, 1996;Song et al, 2008;Tao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%